Analysis of the revolving vane (RV-0) expander, part 1 : experimental investigations - Subiantoro, Alison (2013)
A revolving vane expander prototype based on the RV-0 mechanism design has been fabricated and tested. The range of operational conditions studied is of suction pressures of up to 6 bar (abs) with a constant discharge pressure of 1 bar (abs) and operational speeds of up to 900 rpm. The machine has been shown to work without any significant operational problem in the range of operational conditions tested. The analysis includes the effects of various operational pressures and speeds to the flow rate, leakage and mechanical performances of the expander. The findings show that the prototype machine has the volumetric efficiency of up to 55% with the major leakage paths due to the lip seal and at the radial clearances, contributing to around 50% and 40% of the total leakage, respectively. The isentropic efficiency was found to be up to 17.5% with the frictional losses caused mainly by the journal bearings.